KUALITAS KREDIT SEBAGAI PEMODERASI PENGARUH TINGKAT PENYALURAN KREDIT DAN BOPO PADA PROFITABILITAS - Eka Novita Dewi, Ni Putu; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2016)
The aim of the study is to determine the effect of credit distribution and OEOI on profitability and credit quality as a moderating influence. This research was conducted in LPD located in Tabanan regency as many as 307 LPD. The total of samples that ultimately used in this study as many as 745 observation with the  five years observation, period 2010-2014. Sample selection is done by using purposive sampling method with the four criteria. The analysis technique used in this research is multiple linear regression analysis and moderated regression analysis. The results of the study found that credit distribution has positive effect on profitability, OEOI has negative effect on profitability, credit quality weaken the influence of credit distribution on profitability and credit quality are not able to moderate influence of OEOI on the profitability.
Keywords: profitability, credit distribution, OEOI